2012
DOI: 10.1016/j.jhep.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization for hepatocellular carcinoma

Abstract: Radioembolization is a form of brachytherapy in which intra-arterially injected (90)Y-loaded microspheres serve as sources for internal radiation purposes. It produces average disease control rates above 80% and is usually very well tolerated. Main complications do not result from the microembolic effect, even in patients with portal vein occlusion, but rather from an excessive irradiation of non-target tissues including the liver. All the evidence that support the use of radioembolization in HCC is based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(146 citation statements)
references
References 74 publications
3
136
1
Order By: Relevance
“…Moreover, 99m Tc MAA images are not considered to be ideal method to predict the actual distribution of the 90 Y microspheres. Recent reports have postulated that there is a discordance between 99m Tc MAA and 90 Y microsphere bremsstrahlung SPECT [12,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 99m Tc MAA images are not considered to be ideal method to predict the actual distribution of the 90 Y microspheres. Recent reports have postulated that there is a discordance between 99m Tc MAA and 90 Y microsphere bremsstrahlung SPECT [12,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…But the effective rates became 80% with the EASL criteria (Bruno et al 2012, Lewandowski et al 2009. Recent studies show that the mRECIST criteria could be more objective.…”
Section: Curative Effect Evaluation Methods and The Treatment Time Of mentioning
confidence: 99%
“…The side effect of radiation embolism is relatively weak, manifested as fatigue, mild abdominal pain or discomfort, with or without cachexia, elevated bilirubin and similar flu-like symptoms, some experts call it post-radioembolization syndrome (Bruno S, et al, 2012). The incidence of PRS reported by literature is 12% to54% (Hyun Young Woo and Jeong Heo, 2015), and self-relieved within ten hours.…”
Section: The Side Effect Of Traementioning
confidence: 99%
“…Although it has been postulated that the optimal combination of specific activity and embolic load is somewhere between that of GMS and RMS [37], recent work shows that the overall survival of patients treated with either GMS or RMS across different HCC stages is quite consistent [38]. A multicentre study of hepatic metastatic neuroendocrine tumours showed a statistically significant greater median absorbed dose to liver lobes delivered using GMS (right 117 Gy, left 108 Gy), than using RMS (right 50.8 Gy, left 44.5 Gy), although a similar disease control rate for both (92% GMS and 94% RMS were partial responders or stable disease) after 6 months [39].…”
Section: Differences Between Rms and Gmsmentioning
confidence: 99%